Adaptive Systems in Control and Signal Processing 1983 : proceedings of the IFAC workshop, San Francisco, USA, 20-22 June, 1983 - Landau, Yoan D., 1938-; Tomizuka, M.; Auslander, David M. (IFAC proceedings series., 1984)
Adaptive Systems in Control and Signal Processing 1983.